Net Art: Internet Artists and Their Creative Output (Not Only) Online - Myślak, Dominika Agata; Siudak, Martyna Małgorzata (Media - Culture - Social Communication, 2019)
By the 2020s, electronic media and the functioning of an artist on the Internet will have become an indispensable element of artistic creativity. Along with the evergrowing access to the Internet, an alternate world of art is now being created outside of art galleries. The freedom offered by the Web has influenced newer and newer forms of expression – memes and remixes – each being a part of net art. The aim of the article is to present the phenomenon of Internet artists and their work and to discuss their transfer from the Internet to the real world, including the traditional media.